A Case Report of Thalamic Infarction after Lumbar Drain: A Unique Cause of Perioperative Stroke? - Daniel N. Kianpour; Thomas M. Nguyen; Arthur M. Lam (Case Reports in Anesthesiology)
In the case presented, a patient has an unexplained episode of hypertension during aneurysm clipping. Following the procedure, the patient was discovered to have bilateral thalamic infarctions unrelated to the vascular location of the aneurysm. After a review of the case, it becomes apparent that intracranial hypotension caused by lumbar over drainage of cerebrospinal fluid (CSF) is the likely cause of both the episode of intraoperative hypertension and the thalamic infarcts. It is often presumed that having an open dura protects against intracranial hypotension and subsequent herniation. We present this case to suggest that opening the dura might not be protective in all cases and anesthesiologists must pay particular attention to the rate of CSF drainage. Lumbar CSF drainage is a technique frequently employed during neurological surgery and it is important for anesthesiologists to understand the signs, symptoms, and potential consequences of intracranial hypotension from rapid drainage.